The strike is for everyone - Unknown (Tufts Archival Research Center, 2018)
Depicts a hand holding an olive branch. Text on the sleeve of the hand reads "The strike / Is For / Everyone," and text adjacent to the hand reads "Join / The / Strike / For / Peace". This is a scan of one of three duplicate posters in the folder.